Queen's Royal College, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Exterior, front view of the Queen’s Royal College (QRC), a public, secondary, school for boys, at Maraval Road, Queen's Park West, Port of Spain, Trinidad. Designed by Daniel M. Hahn, qualified architect and past student of QRC, it was opened here 25 March, 1904, on lands that were once part of the government farm, St. Clair. The Queen's Park Savannah is in the foreground of this photograph.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; 1947; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Palms--Trinidad and Tobago; Fences--Trinidad and Tobago; Windows--Trinidad and Tobago; Savannas--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago); Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)